COMPARATIVE ANALYSIS OF THE VALUATION OF FAIR STOCK PRICES USING THE PRICE BOOK RATIO AND PRICE EARNING RATIO METHODSIDX30 ON THE INDONESIAN STOCK EXCHANGE PERIOD 2018 – 2020 - M. Dandi Naparin; SYAFRINADINA (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2023)
This study aims to find out the fair price of shares on the IDX30 index using the Price Book Ratio and Price Earning Ratio Methods. To find out the condition of the stock price of each company belonging to the undervalued or overvalued category based on the results of the valuation using the Price Book Ratio and Price Earning Ratio Methods. The variables used consist of independent variables and dependent variables. The independent variables in this study are PBV (bvs, pbv) and PER (eps, per) while the dependent variable is stock price. This research was conducted on the Indonesian Stock Exchange (IDX) because the dependent variable in this study is the Fair Price of Shares at IDX 30 on the Indonesia Stock Exchange for the 2018-2020 period. The types of data used are qualitative and quantitative as well as the data sources used are primary data and secondary data. The data collection technique is by literature study and documentation. As for data analysis using homogeneity test. From the research results, it was obtained that the significant value of the Price to Book Value (PBV) variable was 0.118 > 0.05. Meanwhile, the Price Earning Ratio (PER) variable has a homogeneity value of 0.199 > 0.05. Based on the test of the coefficient of determination, the value of the fair share price ratio is influenced by the Price to Book Value comparison method and the Price Earning Ratio. Partial and simultaneous tests show that fair share prices are influenced by the Price to Book Value comparison method and the Price Earning Ratio both partially and simultaneously.